Factors influencing Industrialized Building System (IBS) project performance: a systematic review - Yusmin, Jaafar; Lee, Chia Kuang (Universiti Malaysia Pahang, 2020)
Industrialized Building System (IBS) is a form of construction with focused processes comprise of methods, products and a set of connected components which work together to achieve objectives. Malaysian construction industry is one of contributors towards the development of the country. To ensure vitality of construction performance, utilization and application of IBS is the right system to shift to from the current conventional construction method. Adaptability of IBS in Malaysia’s construction industry isvery low due to various limitations and barriers. To better understand IBS, this paper performs a systematic review of studies underpinning the factors influencing IBS success. From a total of 111 articles reviewed in this paper, 16 factors were highly mentioned, such as knowledge and expertise, cost of construction, training, Communication, Lean Construction, Government Policies, Contractors’ Satisfaction, Integration of Resources, Utilization of Software, Market Factor, On-site Management, Technical factor, Integrated Processes Assessment, Management Factor, Payment Issues, and Employee Empowerment. These factors significantly influence IBS project performance.